Were the 40 years of "radical pluralism" a waste of time? A response to Peter Ackers and Patrick McGovern - Paul Edwards (University of Warwick, Industrial Relations Research Unit, 2014)
This paper defends a materialist analysis of employment relations against two recent critiques, by Peter Ackers and Patrick McGovern. 'Radical pluralism' is Ackers's preferred term. The critiques are useful in exposing some ritualistic uses of terms such as conflict, contradiction, and antagonism. Yet they do not damage the core of a materialist view, as opposed to some ways in which it has been deployed. Their central problem is a confusion of levels of analysis. Materialism does not say that concrete experience in the workplace can be read off from fundamental features of the employment relationship, and it does not assert or assume that conflict is the norm at the concrete level. Instead, it offers different levels of analysis. There remain, however, issues of its application to contemporary capitalism, and these are indicated.
Keywords: 330